Cytogenetics study and characterization of sumatra serow, Capricornis sumatraensis (Artiodactyla, Bovidae) by classical and FISH techniques - Sitthisak Jantarat (2018)
© 2017 The Japan Mendel Society. Karyological analysis in the Sumatra serow (Capricornis sumatraensis) from Thailand were conducted. Blood samples were taken from two male and two female serows. After standard whole blood lymphocytes had been cultured at 37°C for 72 h in the presence of colchicine, metaphase spreads were performed on microscopic slides and air-dried. Conventional, GTG-, high-resolution, Ag-NOR banding and fluorescence in situ hybridization (FISH) were applied to stain the chromosomes. The results showed that the diploid chromosome number of C. sumatraensis was 2n=48 and the fundamental number (NF) for both sexes were 60. The types of autosomes were 2 large metacentric, 4 large submetacentric, 2 large acrocentric, 2 medium telocentric, 4 small submetacentric and 32 small telocentric chromosomes. The X chromosome was a medium telocentric chromosome and the Y chromosome was a smallest telocentric chromosome. From the GTG-banding and high-resolution techniques, the numbers of bands in the C. sumatraensis were 147 and 207, respectively, and each chromosome pair could be clearly differentiated. In addition, the long arm near telomere (subtelomeric region) of chromosome pairs 2, 3 and 4 showed clearly observable heteromorphic nucleolar organization regions (NORs) (2a2b, 3a3b, 4a4b). This is the first report on natural polymorphism of NORs. The microsatellites d(AC) 15 accumulated at the telomeres of several pairs and interstitial sites of some chromosomes. The microsatellites d(CGG) 10 highly accumulated at the correspondence sites of NORs. FISH with the telomeric probe revealed hybridization signals on each telomere of all chromosomes and interstitial telomeric sites were not detected. The karyotype formula could be deduced as: {equation presented}